PENGENDALIAN HAMA KUMBANG TANDUK MENGGUNAKAN POC AIR NIRA DAN NANAS PADA TANAMAN KELAPA SAWIT DI DESA BINANGA DUA KABUPATEN LABUHAN BATU SELATAN - Hidayat, Rahmat; Rizal, Khairul; Putri Septyani, Ika Ayu; Adam, Dini Hariyati (Agros Journal of Agriculture Science, 2024)
This research aims to test the effectiveness of using liquid organic fertilizer (LOF) from sap and pineapple water in controlling horn beetle pests (Oryctes rhinoceros) on oil palm plants in private plantations in Tandikat hamlet, Silangkitang. The approach used was a Randomized Block Design (RBD) with four treatments, namely N0 (control), N1 (100% pineapple starch), N2 (500 grams of pineapple + 1 liter LOF of palm juice), and N3 (500 grams of pineapple + 2 liters of LOF sap water) each repeated four times. The parameters observed included the number of horn beetles caught and those that died. The results of the analysis of variance showed that the significance value of the treatment was <0.05, indicating that there was a real effect of the treatment on the number of horn beetles caught and killed. Duncan's Multiple Range Test (DMRT) further test indicated that the N0 treatment was significantly different from the N2 and other treatments. N2 treatment proved to be the best treatment, showing high effectiveness in controlling horn beetle pests. The conclusion of this research is that the use of LOF from pineapple and palm juice is significantly effective in controlling horn beetle pests on oil palm and is an environmentally friendly alternative to the use of chemical pesticides.Keywords: pests; horn beetles; liquid organic fertilizer; pineapple